Effectiveness of Web-based Instruction in Terms of Achievement of Class IX Mathematics Students of Jawahar Navodaya Vidyalaya - Jhariya, alram Prasad; Shinde, Laxman (JOURNAL OF INDIAN EDUCATION, 2016)
The present study was done on Class IX students of Jawahar Navodaya Vidyalayas of Madhya Pradesh and Chhattisgarh. About 316 students were selected as sample by using random sampling technique. Using Self-developed Achievement Test in Mathematics and Advanced Progressive Matrices of J.C. Raven (1953) it is found that the (i) Adjusted mean scores of achievement in mathematics of Web-based Instruction (WbI) group is significantly higher than that of traditional method group when the groups were matched with respect to pre-achievement in Mathematics. (ii) Achievement in mathematics is independent of economic status when the groups were matched with respect to pre-achievement in mathematics. (iii) There is no significant effect of the interaction between treatment and economic status when the groups were matched with respect to pre-achievement in mathematics.